2017
DOI: 10.1080/10538712.2017.1292338
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Socially Advantaged and Disadvantaged Turkish Mothers’ Views About Training on Preventing Children From Sexual Abuse

Abstract: This study aims to investigate the views of socially advantaged (N = 8) and disadvantaged mothers (N = 8) whose children are aged between 48 and 66 months old about the issue of sexual abuse before and after the training provided to them. The views of mothers in both groups were investigated before and after the 5-week experience-based training about my body belongs to me, knowing and expressing feelings, good and bad touch, good and bad secrets, knowing how to say no, and help resources. The data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…In Bayley et al [45] study based on the Theory of planned behavior, attitude predicted the intention. Results of the present study are in good agreement with the results of Sanberk et al [46], who investigated the attitude of Turkish mothers having a child with the age of 48-66 months and revealed that educational intervention caused the increase in participants' attitude, and also with the study of Khani Jeihooni et al [47] who studied prevention behaviors from sexually transmitted diseases. Nagpal et al [3] indicated that important changes had been created in parents' attitudes toward sexual training in children, and in recent years, parents' attitudes have changed from negative to The mean score of perceived behavioral control had significant enhancement in the experimental group 3 months after the intervention, while the control group had no changes.…”
Section: Discussionsupporting
confidence: 92%
“…In Bayley et al [45] study based on the Theory of planned behavior, attitude predicted the intention. Results of the present study are in good agreement with the results of Sanberk et al [46], who investigated the attitude of Turkish mothers having a child with the age of 48-66 months and revealed that educational intervention caused the increase in participants' attitude, and also with the study of Khani Jeihooni et al [47] who studied prevention behaviors from sexually transmitted diseases. Nagpal et al [3] indicated that important changes had been created in parents' attitudes toward sexual training in children, and in recent years, parents' attitudes have changed from negative to The mean score of perceived behavioral control had significant enhancement in the experimental group 3 months after the intervention, while the control group had no changes.…”
Section: Discussionsupporting
confidence: 92%
“…Sanberk et al . 's[ 16 ] finding in 2017 on the views of Turkish mothers who had a 16 to 48 month old child and were trained in sexual abuse prevention, increased their attitude's score. The results of Bakhshi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Discussing inappropriate issues about sexuality with children are considered that it may increase the potential of child abuse (Kucuk, 2016). It is stated that the word "sexual" occurs only once in preschool curriculum textbooks of the Turkish Ministry of National Education and this is while defining sexual abuse (Sanberk et al, 2017). As sexuality is a taboo concept, it is difficult for children to comprehend.…”
Section: Personal Safetymentioning
confidence: 99%
“…A study conducted in Turkey found that 75% of CSA victims delay reporting the incident (Koçtürk & Yüksel, 2018). In Turkey, a standard program for the prevention of CSA is not included as a part of the preschool curriculum (Sanberk et al, 2017). All such findings show that there is a need for children to acquire skills to protect against sexual abuse in Turkey.…”
mentioning
confidence: 99%